Implementation of Halal Industry Policy as A Support for Halal Tourism In Lombok - Ni Putu Deby Angraini; Ida Ayu Oka Martini (Eduvest - Journal of Universal Studies, 2024)
In recent years, Lombok has emerged as a leading halal tourist destination in Indonesia and globally, supported by halal policies aimed at attracting Muslim and local tourists. These policies, including the Regional Regulation of West Nusa Tenggara Province Number 2 of 2016 on Halal Tourism and Law Number 33 of 2014 on Halal Product Guarantee, have positively impacted the tourism industry. This study addresses three main questions: (1) How are halal industry policies implemented to support halal tourism in Lombok? (2) How has the halal industry developed to support this tourism? (3) What are the supporting and inhibiting factors in implementing these policies?. The research is descriptive with a qualitative approach, using primary data from interviews and secondary data from relevant documents. Purposive sampling was employed,  targeting officials from the West Nusa Tenggara Provincial Tourism and Industry Offices, the Indonesian Ulema Council of West Nusa Tenggara, tourism business actors, MSMEs, foreign and domestic tourists, and local communities. Data collection involved interviews, observation, and documentation, with data analysis through reduction, collection, and summarization. The study finds that implementing halal industrial policies has increased Muslim tourist numbers and  strengthened Lombok's image as a halal destination. However, challenges remain, such as developing specialized halal tourism areas according to regional regulations without disrupting conventional tourism, improving services, providing halal facilities, and offering education and training for industry players.